Eco-evolutionary feedbacks link prey adaptation to predator performance. (20th November 2019) - Fryxell, David C.; Wood, Zachary T.; Robinson, Rebecca; Kinnison, Michael T.; Palkovacs, Eric P.
Abstract : Eco-evolutionary feedbacks may determine the outcome of predator–prey interactions in nature, but little work has been done to quantify the feedback effect of short-term prey adaptation on predator performance. We tested the effects of prey availability and recent (less than 100 years) prey adaptation on the feeding and growth rate of largemouth bass ( Micropterus salmoides ), foraging on western mosquitofish ( Gambusia affinis ). Field surveys showed higher densities and larger average body sizes of mosquitofish in recently introduced populations without bass. Over a six-week mesocosm experiment, bass were presented with either a high or low availability of mosquitofish prey from recently established populations either naive or experienced with bass. Naive mosquitofish were larger, less cryptic and more vulnerable to bass predation compared to their experienced counterparts. Bass consumed more naive prey, grew more quickly with naive prey, and grew more quickly per unit biomass of naive prey consumed. The effect of mosquitofish history with the bass on bass growth was similar in magnitude to the effect of mosquitofish availability. In showing that recently derived predation-related prey phenotypes strongly affect predator performance, this study supports the presence of reciprocal predator–prey trait feedbacks in nature.